Liquid Smoke as an Alternative to Prevent Crop Failure in Rice Fields in Rasau Jaya Dua Village - Agustina, Via; Anasi, Putri Tipa; Ulfah, Maria; Harjanti, Diah Trismi (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to analyse the use of liquid smoke as an alternative to prevent crop failure in rice harvests in Rasau Jaya Dua Village. The research method used is descriptive qualitative with data sources obtained through interviews with liquid smoke producers, long-time liquid smoke users, and new liquid smoke users who use it on rice plants. The results of the study show that the use of liquid smoke can help prevent crop failure in rice plants, which is often caused by pest and disease attacks. Liquid smoke is believed to increase plant resistance to pests and also acts as a fertiliser for the soil. Most farmers in Rasau Jaya Dua Village have tried various methods of preventing crop failure, such as the use of pesticides, but the use of liquid smoke as a new solution is still limited. Farmers' responses to liquid smoke users vary. Most welcome this technology because it is considered environmentally friendly and effective, although there are obstacles such as limited knowledge and difficulties in its application. Therefore, further socialisation and training are needed to increase farmers' understanding and skills in the use of liquid smoke. This training is expected to contribute to the development of more sustainable agricultural technology in the future.